2017
DOI: 10.1016/j.ejca.2017.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Amide proton transfer-weighted magnetic resonance image-guided stereotactic biopsy in patients with newly diagnosed gliomas

Abstract: Purpose Pathological assessment using WHO criteria is the gold standard for diagnosis of gliomas. However, the accuracy of diagnosis is limited by tissue sampling, particularly for infiltrating, heterogeneous tumors. We assessed the accuracy of amide proton transfer-weighted (APTw) MRI-guided tissue sampling to identify regions of high-grade glioma via radiographic-histopathologic correlation in patients with newly suspected glioma. Patients and methods Twenty-four patients with previously undiagnosed glioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 84 publications
(101 citation statements)
references
References 38 publications
5
92
0
Order By: Relevance
“…Their use for the evaluation of treatment response may be investigated in the future. Nevertheless, the conventional MTR asymmetry analysis has been demonstrated to be applicable in many clinical applications, including tumor identification, glioma grading, treatment response evaluation, and so on, with its feasibility well validated by biopsy or histology . Additionally, it has been demonstrated that the APTw image contrast in the tumor is mostly attributable to the APT contribution under similar RF powers as used here .…”
Section: Discussionmentioning
confidence: 80%
“…Their use for the evaluation of treatment response may be investigated in the future. Nevertheless, the conventional MTR asymmetry analysis has been demonstrated to be applicable in many clinical applications, including tumor identification, glioma grading, treatment response evaluation, and so on, with its feasibility well validated by biopsy or histology . Additionally, it has been demonstrated that the APTw image contrast in the tumor is mostly attributable to the APT contribution under similar RF powers as used here .…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, it is an important feature that, in cases with high‐grade gliomas without gadolinium enhancement, APTw‐hyperintense foci are still clearly visible within the lesions . Notably, a recent study using APTw image‐guided stereotactic biopsy by Jiang et al suggests that APTw imaging can identify high‐grade regions within heterogeneous gliomas, allowing more precise sampling of the highest‐grade region of a tumor. On the other hand, in patients with pathologically confirmed low‐grade gliomas, including those with gadolinium enhancement, APTw imaging shows isointensity or scattered punctate hyperintensity within the lesion.…”
Section: Current Applicationsmentioning
confidence: 99%
“…Figures show some examples of these parameters in a human study at 3 T, confirming the minimizing of normal tissue and edema signal into the background and a strong tumor contrast. These saturation parameters were also used in the validation studies with APTw MRI‐directed biopsies . For other applications, the optimal parameters and analysis approaches are still under development.…”
Section: Challenging Issues and Controversiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The CEST method can enhance the detection sensitivity of low‐concentration metabolites in vivo when repeated saturation transfer allows for an accumulation and amplification of the MRI signals derived from metabolite‐specific solute pools. Biomolecules that are detectable by various CEST techniques include polypeptides using amide proton transfer (APT), glycogen with “glycoCEST,” glycosaminoglycan by “gagCEST,” glutamate by “GluCEST,” glucose by “glucoCEST,” and creatine by “CrCEST.” Indeed, CEST MRI has been applied in patients with brain tumors, prostate cancer, breast cancer, and stroke using APT, osteoarthritis using gagCEST, epilepsy using GluCEST, and brain tumors using glucoCEST . Despite its great promise, the clinical use of CEST MRI is limited by the long acquisition times needed to acquire multiple frames at different saturation offset frequencies, and for quantification …”
Section: Introductionmentioning
confidence: 99%